Exploratory Data Analysis (EDA): A Study of Olympic Medallist - Noviyanti T M Sagala; Fonggi Yudi Aryatama (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2022)
Olympic games are one of the most popular international sports events in the world where thousands of athletes participate in different types of sports categories. The winner has rewarded a medal (Bronze, Silver, Gold) according to the rank. An analysis can be carried out on the Olympic data to understand the changes in medalists over time. Furthermore, it helps to determine the progress of participating countries and strategies that can be used in the future. Exploratory Data Analysis (EDA) is a method for analyzing and summarizing the properties of data, either in graphical or non-graphical, to get insights from the dataset being studied. The approaches can be classified as univariate, bivariate, or multivariate. EDA is widely used in various domains including sport. The main purpose of this study is to analyze the changes of Olympic Medalist data throughout the provided years in the form of univariate, bivariate, and multivariate analysis. This analysis provides detailed, statistical, and interesting information about the changes in medal winners from time to time.